Estrés académico en estudiantes que cursan asignaturas de Física en ingeniería: dos casos diferenciados en Colombia y México - Suárez, Oscar Jardey; Ramírez Díaz, Mario Humberto (Revista Científica, 2020)
This document reports the study of the variables underlying academic stress in two differentiated populations of city students who study physics in the engineering faculty (Colombia and Mexico). The inventory used is that of Polo, Hernández and Pozo of 1996 that measures two dimensions: stress responses and stress-producing activities. An additional dimension that considers aspects of the physics class has been considered. The population of university students who participated in each community in each 124 for country. The instrument has a reliability of 0,918 (Col) and 0,937 (Mxn), the Kaiser-Meyer-Olkin sample adequacy measure, 0,838 (Col) and 0,878 (Mxn), the interpreted variance 61,40% (Col) and 64,46% (Mxn). The results show four underlying variables to the student population in Colombia (stress responses [RE] Interaction [I] Evaluation [E] and Activity Extra School [AEE]) while in Mexico there are 3 underlying variables stress (Stress Responses [RE], Evaluation [E] and School Environment [EE]). The stress responses have differences between populations. The evaluation, like other studies, is shown as a variable that underlies academic stress in both populations, however their understanding shows different sources.